The organization man - Whyte, William Hollingsworth, 1917-1999 (Harmondsworth : Penguin, 1960)
"Recognized as a benchmark, Whyte's book reveals the dilemmas at the heart of the group ethos that emerged in the corporate and social world of the postwar era."--Nathan Glazer